The routine use of patient reported outcome measures in healthcare settings. (18th January 2010) - Dawson, Jill; Doll, Helen; Fitzpatrick, Ray; Jenkinson, Crispin; Carr, Andrew J
Abstract : The use of patient reported outcome measures might seem to be quite straightforward; however, a number of pitfalls await clinicians with limited expertise. Jill Dawson and colleagues provide a guide for individuals keen to use patient reported outcome measures at a local level